Geoscience of Climate and Energy 9. History and Governance Models as a Blueprint for Future Federal–Provincial Co-operation on Environmental Monitoring in the Alberta Oil Sands Region - Wallace, Ron R. (Geoscience Canada, 2013)
DOI: http://dx.doi.org/10.12789/geocanj.2013.40.011